Clinical implications of a mechanistic link connecting SARS-Cov-2, diabetes mellitus, Zinc in COVID-19 pathophysiology, and the prophylactics in the treatment of SARS-CoV-2 - Deeptimayee Rout; Atish Kumar Sahoo (Elsevier, 2023)
The global outbreak of COVID-19 is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 causes damage to multiple organs by attaching to angiotensin-converting enzyme 2 (ACE2) receptor. Infected patients with co-morbidities like pulmonary, hepatic, renal, cardiovascular disorder, and diabetes are at higher risk of death. Individuals with diabetes are at higher risk of developing complications with SARS-CoV-2 infection because of abnormal glucose homeostasis, inflammation, insulin resistance, oxidative stress, and HbA1C. On the other hand, the SARS-CoV-2 acts as a diabetogenic agent by binding to ACE2 in pancreatic β-cells causes cellular dysfunction, and elevation in blood glucose level in infected individuals. Zinc plays a pivotal role in storage, secretion, and action on insulin and also, it has antiviral, antioxidant, anti-inflammatory, immunomodulatory properties which has beneficial role on viral respiratory tract infection. Drugs dihydrotanshinone, quabain, saikosaponin B2, silvestrol hold promising antiviral activities on SARS helicase. Even, combination of drugs as interferon β-1b, lopinavir-ritonavir, and ribavirin are used to control viral replication, and inflammation. Luteolin with dexamethasone inhibit cytokine production in SARS-CoV-2. Luteolin, quercetin, and kaempferol downregulate, inhibit the TMPRSS2 expression and 3CLpro preventing viral entry and replication inside the host cell. The current review attempted to elucidate the mechanistic link between COVID-19-pathophysiology, diabetes, insulin, and Zn. The study attempts to formulate "Drug repurposing" with Zinc-supplementation can be used as prototypes to minimize tissue injures by SARS-CoV-2 infection in diabetic. The analysis found Zinc-supplementation with most compatible natural drugs dexamethasone and luteolin, or quercetin/kaempferol provides a cost-effective and minimizes time spent on clinical trials. However, "Drug repurposing" with Zinc supplementation is likely to take several years clinical validation of therapeutic targets before it is deemed efficacious and approved.